Shifting Roles in Families of Deferred Action for Childhood Arrivals (DACA) Recipients and Implications for the Transition to Adulthood. (September 2021) - Aranda, Elizabeth; Vaquera, Elizabeth; Castañeda, Heide
The 2012 Deferred Action for Childhood Arrivals (DACA) program enabled undocumented immigrant young adults to more freely participate in U.S. society. Guided by family systems theory, which emphasizes that individual actors are interdependent with others within family units, we analyze the experiences of young adult DACA recipients while members of their families remain deportable. We draw from 44 in-depth interviews with DACA recipients who are part of mixed-status families to answer three questions: How were the benefits of DACA distributed within mixed-status family units and discrepancies interpreted by recipients? How did obtaining DACA change recipients' roles and responsibilities within their families? And to what extent did obtaining DACA shape young adults' envisioned futures? We discuss potential results of the program, including changes in familial relationships, conflicting roles, and challenges in recipients' efforts at individuation from their families.